Differentiation between Hemolytic Uremic Syndrome and Thrombotic Thrombocytopenic Purpura: A comparison of key laboratory findings between 2010 and 2021 (Research, Society and Development, 2024)
Objective: This article aims to analyze and compare the clinical and laboratory findings related to Thrombotic Microangiopathies (TMAs), specifically Hemolytic Uremic Syndrome (HUS) and Thrombotic Thrombocytopenic Purpura (TTP), to support diagnostic and therapeutic decisions. The study also explores critical biochemical and hematological markers to differentiate these diseases. Methodology: A systematic literature review was conducted using articles from PubMed, Scielo, and Google Scholar, focusing on studies published from 2010 to mid-2021, covering a ten-year period. The review included research on clinical presentations, laboratory findings, and the molecular mechanisms underlying HUS and TTP. Results: The analysis revealed significant overlaps in clinical manifestations, such as anemia, thrombocytopenia, and renal dysfunction, but distinct differences in their pathophysiologies. HUS is associated with complement system dysfunction and Shiga toxin-mediated damage, while TTP is linked to ADAMTS13 enzyme deficiency. Laboratory markers such as lactate dehydrogenase, bilirubin, and platelet count were identified as crucial for differentiating the two conditions. Unique Contribution to Theory, Policy, and Practice: Underscoring the critical clinical and laboratory distinctions between HUS and TTP, this study provides a comprehensive framework for achieving precise diagnoses and developing individualized treatment strategies. Enhancing diagnostic accuracy is paramount to mitigating treatment delays, minimizing complications, and improving patient outcomes. Moreover, this review highlights the imperative need for standardizing diagnostic protocols for TMAs and advocates for further research to address existing knowledge gaps in this field.